Preparation method of Al-Zn-coated Al2O3 composite phase change heat storage material with core-shell structure
By preparing the core-shell structure Al-Zn@Al2O3 composite phase change heat storage material, the problem that traditional phase change materials can only undergo phase change heat storage at specific temperatures is solved, and the regulation of the heat storage temperature domain and efficient thermal management are realized, which is suitable for medium and high temperature environments.
Patent Information
- Application Number
- CN202510090211.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-21
AI Technical Summary
Traditional phase change materials can only undergo phase change and heat storage at a specific temperature, which limits its application range. The liquid metal after solid-liquid phase change has high chemical corrosion and high thermal stress caused by volume expansion.
The preparation method of the core-shell structure Al-Zn@Al2O3 composite phase change heat storage material is adopted. The aluminum powder suspension is ultrasonicized to remove the aluminum oxide film on the surface of the aluminum powder, and the aluminum zinc alloy core and oxide shell are calcined under a protective atmosphere.
The control of the thermal storage temperature domain is achieved, the enthalpy of phase change and thermal conductivity is improved, the strength and density of the oxidized shell are enhanced, and the leakage of liquid alloys is prevented. It is suitable for medium and high temperature environments.
Smart Images

Figure HDA0005251282280000011 
Figure HDA0005251282280000012 
Figure HDA0005251282280000021
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a core-shell structure Al-Zn@Al2O3 composite phase-change thermal storage material, belonging to the technical field of medium- and high-temperature phase-change thermal storage materials. Background Art
[0002] Phase change thermal storage technology has a high thermal storage density and a rapid response in the heat storage and release process. The key to phase change thermal storage technology lies in phase change materials (PCMs). PCMs have the advantages of high energy density, high energy conversion efficiency, excellent recyclability, and can maintain a constant temperature to store and release a large amount of heat during the phase change process. At present, phase change thermal storage materials are mainly divided into organic PCMs, inorganic molten salt PCMs and metal-based PCMs. Due to their low thermal conductivity, organic PCMs and inorganic molten salt PCMs have problems such as excessive supercooling and phase separation during thermal cycles. Metal-based PCMs are particularly important in thermal management and energy regulation due to their superior thermal conductivity and thermal storage density. However, the liquid metal after the solid-liquid phase change has high chemical corrosiveness and high thermal stress caused by volume expansion, which makes the phase change material encapsulation technology come into being. After continuous research, the four more successful encapsulation strategies are metal-metal microcapsules, metal-metal macrocapsules, metal-ceramic microcapsules and metal-ceramic macrocapsules.
[0003] However, the melting point of commonly used phase change materials is often fixed by the characteristics of the material itself, and can only produce enhanced latent heat absorption at a specific temperature point, which limits its scope of application. Therefore, the development of phase change materials with high comprehensive performance is of great significance in future thermal energy storage systems. Summary of the invention
[0004] Aiming at the problem that traditional PCMs can only perform phase change heat storage at a specific temperature, the present invention proposes a preparation method of a core-shell structure Al-Zn@Al2O3 composite phase change heat storage material, that is, dilute hydrochloric acid is added to an aluminum powder suspension after ultrasonic treatment and an ammonium fluoride solution is used to remove the aluminum oxide film on the surface of the aluminum powder, and then a gelatin dispersion solution system is added, which is beneficial to ensure that the aluminum powder surface is fully contacted and reacted with zinc ions, and ethylenediaminetetraacetic acid is complexed with zinc ions, thereby controlling the replacement reaction rate, and roasting under a protective atmosphere can make the zinc coating dissolve in the inner core aluminum to form an aluminum-zinc alloy, and roasting under air can form a stable and dense oxide shell Al2O3 on the alloy surface, and finally form a core-shell structure Al-Zn@Al2O3 composite phase change heat storage material.
[0005] A method for preparing a core-shell structure Al-Zn@Al2O3 composite phase change thermal storage material, the specific steps are as follows:
[0006] (1) Deionized water or ultrapure water are used to prepare aluminum powder turbid solution, HCl solution, NH4F solution, ZnSO4 solution and EDTA mixed solution respectively;
[0007] (2) placing the aluminum powder turbid solution in an ultrasonic bath for 10 to 30 minutes to obtain an aluminum powder suspension;
[0008] (3) adding HCl solution to the aluminum powder suspension, stirring at a temperature of 45 to 65° C. for 5 to 10 minutes, then adding gelatin and reacting at a temperature of 45 to 65° C. for 10 to 20 minutes under stirring to obtain solution A;
[0009] (4) slowly adding NH4F solution to solution A at a temperature of 40 to 60° C. and stirring, and continuing the reaction for 30 to 60 minutes, then adding a mixture of zinc sulfate solution and ethylenediaminetetraacetic acid and reacting for 3 to 5 hours, standing, separating the solid and the liquid, washing the solid alternately with anhydrous ethanol-water-anhydrous ethanol for 3 to 5 times, and drying to obtain solid B;
[0010] (5) In a protective atmosphere, the solid B is heated at a uniform rate to a temperature of 600 to 660° C. and calcined at high temperature for 0.5 to 4 h to obtain an aluminum-zinc alloy powder;
[0011] (6) In an air atmosphere, the aluminum-zinc alloy powder is heated at a uniform rate to a temperature of 750-850°C and calcined for 1-4 h to obtain an Al-Zn@Al2O3 high-temperature phase change thermal storage material with a core-shell structure.
[0012] Preferably, in the step (1), the molar ratio of aluminum powder, hydrochloric acid, NH4F, zinc sulfate and EDTA is 92:(5-20):(15-25):(20-60):(30-70), the concentration of HCl solution is 0.05-0.20 mol / L, the concentration of NH4F solution is 0.15-0.25 mol / L, the concentration of ZnSO4 solution is 0.28-0.56 mol / L, and the concentration of EDTA solution is 0.31-0.62 mol / L.
[0013] Preferably, the mass ratio of gelatin to aluminum powder in the aluminum powder suspension in step (3) is 1:(2-50).
[0014] Preferably, the dropping rate of the NH4F solution in step (4) is 2 to 5 mL / min.
[0015] Preferably, the dropping rate of the mixed solution of zinc sulfate solution and ethylenediaminetetraacetic acid in step (4) is 2 to 5 mL / min.
[0016] Preferably, the protective atmosphere in step (5) is N2 atmosphere or inert atmosphere, and the uniform heating rate is 5 to 30°C / min.
[0017] Preferably, the uniform heating rate in step (6) is 5 to 30° C. / min.
[0018] The present invention controls different galvanizing amounts to form aluminum-zinc alloys with different melting points, thereby achieving regulation of the heat storage temperature range. The heat regulation range is that Al-Zn absorbs heat to undergo solid-liquid phase transition, thereby achieving the effect of heat storage and temperature control. When the external temperature decreases, the heat storage core releases the stored heat and undergoes liquid-solid transition to slow down the temperature drop of the hot bed. In this process, since the oxide shell has high strength and density, leakage of the liquid alloy can be prevented.
[0019] In the present invention, gelatin is added to disperse aluminum powder to increase its reaction contact area, hydrochloric acid and ammonium fluoride solution are added to remove aluminum powder aluminum oxide film, and ethylenediaminetetraacetic acid is added to complex with zinc ions to buffer the reaction between aluminum powder and zinc ions, thereby making the replaced zinc coating more uniform and dense, which is beneficial to the formation of alloy in the later stage; calcination under inert atmosphere and air is to sequentially generate alloy and oxide shell, and finally prepare Al-Zn@Al2O3 composite phase change thermal storage material with core-shell structure, which realizes the regulation of thermal storage temperature range of phase change thermal storage material under the premise of ensuring reliable cycle stability, and maintains a high thermal storage density, so as to realize efficient utilization of energy.
[0020] The beneficial effects of the present invention are:
[0021] (1) The heat storage temperature range of the heat storage material in the existing heat storage technology is generally affected by the melting point of the phase change core, resulting in a fixed heat storage temperature, which is not universally applicable. However, the core-shell structure Al-Zn@Al2O3 composite phase change heat storage material prepared based on micron-grade aluminum powder in the present invention can adjust the phase change temperature of the original pure aluminum from 660°C to the low eutectic point of the solid solution aluminum-zinc alloy of 618.5°C, and the phase change temperature can be adjusted by adjusting the aluminum-zinc molar ratio in the alloy, so as to be suitable for heat storage requirements in different temperature ranges;
[0022] (2) The aluminum-zinc alloy phase-change heat storage material prepared based on micron-grade aluminum powder of the present invention is wrapped by an aluminum oxide shell layer, which is both resistant to high temperatures and has enhanced mechanical strength. Its microcapsule structure can increase the heat exchange area and the sealing performance of the package;
[0023] (3) The aluminum-zinc alloy phase-change thermal storage material prepared based on micron-grade aluminum powder of the present invention has a higher phase-change enthalpy value and thermal conductivity, and has a higher thermal storage density and thermal conductivity than traditional non-metallic thermal storage materials, which is beneficial to improving heat transfer efficiency;
[0024] (4) The present invention adopts roasting in an inert atmosphere to prevent metal oxidation and make the composition of the generated aluminum-zinc alloy uniform, which is conducive to the formation of the oxide shell Al2O3 during the subsequent oxidation roasting process, ensuring that it has good uniformity and density;
[0025] (5) The phase change temperature range of the aluminum-zinc alloy core of the core-shell structure Al-Zn@Al2O3 composite phase change thermal storage material of the present invention is 618.5-646.9°C, and the aluminum oxide of the coating layer has good high temperature resistance and high strength and density, which can be used in medium and high temperature environments and is more likely to meet industrial needs;
[0026] (6) The raw materials of the present invention are cheap and readily available, and compared with the chemical zinc plating method, the process is simpler and more controllable, and can be mass-produced;
[0027] (7) The core-shell structure composite phase change thermal storage material powder of the present invention can be processed into blocks or components of various shapes, which is convenient for construction when used in the fields of solar collectors, waste heat recovery devices, etc., and is suitable for different application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The SEM images of the original aluminum powder and the Al@Zn prepared in Examples 1 to 3;
[0029] Figure 2 The SEM image and partial cross-section scanning EDS image of the core-shell structure Al-Zn@Al2O3 composite phase change thermal storage material prepared in Example 1 after oxidation calcination at 800°C;
[0030] Figure 3 The DSC endothermic and exothermic characteristic diagrams of the core-shell structure Al-Zn@Al2O3 composite phase change thermal storage materials prepared in Examples 1 to 3, (a) is the DSC endothermic curve of Al-Zn@Al2O3 after calcination of Al-Zn alloys with different zinc concentrations at 800°C, and (b) is its exothermic curve.
[0031] Figure 4 XRD patterns of Al@Zn and aluminum-zinc alloy powders prepared in Examples 1 to 3, (a) is Al@Zn, and (b) is aluminum-zinc alloy powder. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.
[0033] Example 1: A method for preparing a core-shell structure Al-Zn@Al2O3 composite phase change thermal storage material, the specific steps are as follows:
[0034] (1) respectively adding aluminum powder, hydrochloric acid, NH4F, zinc sulfate, and ethylenediaminetetraacetic acid into deionized water to prepare aluminum powder turbid solution, HCl solution, NH4F solution, ZnSO4 solution, and ethylenediaminetetraacetic acid solution; wherein the molar ratio of aluminum powder, hydrochloric acid, NH4F, zinc sulfate, and ethylenediaminetetraacetic acid is 92:20:20:28:31, the concentration of HCl in hydrochloric acid is 0.2 mol / L, the concentration of NH4F solution is 0.2 mol / L, the concentration of ZnSO4 solution is 0.28 mol / L, and the concentration of ethylenediaminetetraacetic acid solution is 0.31 mol / L;
[0035] (2) placing the aluminum powder turbid solution in an ultrasonic bath for 20 min to obtain an aluminum powder suspension; wherein the ultrasonic power is 80 W;
[0036] (3) adding HCl solution to the aluminum powder suspension, stirring at 50° C. for 5 min, then adding gelatin and reacting at 50° C. for 15 min under stirring to obtain solution A;
[0037] (4) At a temperature of 50° C. and under stirring conditions, NH4F solution was slowly added to solution A at a drop rate of 2 mL / min and the reaction was continued for 30 min, and then zinc sulfate solution and ethylenediaminetetraacetic acid solution were added at a drop rate of 2 mL / min and reacted for 3 h. The solution was allowed to stand for 80 min, solid-liquid separation was performed, and the solid was washed three times in the order of anhydrous ethanol-water-anhydrous ethanol, and then dried in vacuo at 70° C. to obtain solid B;
[0038] (5) Under protective atmosphere (nitrogen), the solid B is heated at a rate of 20°C / min to a temperature of 650°C and calcined for 30 min to obtain aluminum-zinc alloy powder;
[0039] (6) In an air atmosphere, the aluminum-zinc alloy powder was uniformly heated at a heating rate of 10°C / min to a temperature of 800°C and calcined for 2 h to obtain an Al-Zn@Al2O3 high-temperature phase change thermal storage material with a core-shell structure;
[0040] The SEM image of the aluminum-zinc alloy powder, an intermediate product of the core-shell structure Al-Zn@Al2O3 composite phase change thermal storage material prepared in this embodiment, is as follows: Figure 1 As shown, from Figure 1 It can be seen that the galvanizing effect of aluminum powder is significant. Zinc is basically wrapped on the surface of aluminum powder to form a sphere, and there is no agglomeration phenomenon, which is conducive to a more uniform distribution of the aluminum-zinc alloy formed later and a tighter wrapping of the aluminum-zinc composite oxide shell.
[0041] The SEM and EDS images of the core-shell structure Al-Zn@Al2O3 aluminum-zinc alloy phase change thermal storage material of this embodiment are shown in Figure 2 As shown, from Figure 2It can be seen that the surface shell of the core-shell structure Al-Zn@Al2O3 aluminum-zinc alloy phase change thermal storage material is thick and dense, and the coverage is uniform and well wrapped;
[0042] The DSC heat absorption and release characteristics of the core-shell structure Al-Zn@Al2O3 aluminum-zinc alloy phase change thermal storage material prepared in this embodiment are shown in the figure. Figure 3 As shown, (a) is the DSC endothermic curve of Al-Zn@Al2O3 after calcination at 800℃ for Al-Zn alloys with different zinc concentrations, and (b) is its exothermic curve; Figure 3 From the middle curve O-1, it can be seen that the main endothermic peak is at 646.9℃, and the main exothermic peak is at 610.1℃, which means that the storage and release temperature range of the material is located near this. The single phase change main peak shown can indicate that the material prepared under this concentration of zinc sulfate solution can almost completely form a solid solution aluminum-zinc alloy; and the melting heat and solidification heat values of MEPCMs are both large, and the difference between the melting heat and the solidification heat is very small, indicating that the material has excellent thermal storage density and low supercooling, which is conducive to ensuring high energy storage density and improving heat conduction efficiency.
[0043] Example 2: A method for preparing a core-shell structure Al-Zn@Al2O3 composite phase change thermal storage material, the specific steps are as follows:
[0044] (1) respectively adding aluminum powder, hydrochloric acid, NH4F, zinc sulfate, and ethylenediaminetetraacetic acid into deionized water to prepare aluminum powder turbid solution, HCl solution, NH4F solution, ZnSO4 solution, and ethylenediaminetetraacetic acid solution; wherein the molar ratio of aluminum powder, hydrochloric acid, NH4F, zinc sulfate, and ethylenediaminetetraacetic acid is 92:20:20:42:46, the concentration of HCl in hydrochloric acid is 0.2 mol / L, the concentration of NH4F solution is 0.2 mol / L, the concentration of ZnSO4 solution is 0.42 mol / L, and the concentration of ethylenediaminetetraacetic acid solution is 0.46 mol / L;
[0045] (2) placing the aluminum powder turbid solution in an ultrasonic bath for 10 min to obtain an aluminum powder suspension; wherein the ultrasonic power is 100 W;
[0046] (3) adding HCl solution to the aluminum powder suspension, stirring at 45° C. for 20 min, then adding gelatin and reacting at 45° C. with stirring for 20 min to obtain solution A;
[0047] (4) At a temperature of 40° C. and under stirring conditions, NH4F solution was slowly added to solution A at a drop rate of 3 mL / min and the reaction was continued for 40 min, and then zinc sulfate solution and ethylenediaminetetraacetic acid solution were added at a drop rate of 4 mL / min and reacted for 4 h. The solution was allowed to stand for 50 min, solid-liquid separation was performed, and the solid was washed three times in the order of anhydrous ethanol-water-anhydrous ethanol, and then vacuum dried at 60° C. to obtain solid B;
[0048] (5) Under protective atmosphere (argon), the solid B was heated at a rate of 25°C / min to a temperature of 600°C and calcined for 3.5 h to obtain aluminum-zinc alloy powder;
[0049] (6) In an air atmosphere, the aluminum-zinc alloy powder was heated at a rate of 15°C / min to a temperature of 750°C and calcined for 4 h to obtain an Al-Zn@Al2O3 high-temperature phase change thermal storage material with a core-shell structure;
[0050] The DSC heat absorption and release characteristics of the core-shell structure Al-Zn@Al2O3 composite phase change thermal storage material prepared in this embodiment are shown in the figure. Figure 3 As shown, from Figure 3 Curve O-2 shows that the main peak of endothermic absorption is 630.5℃, and the main peak of exothermic release is 613.9℃, which means that the storage and release temperature range of the material is located near this. The single phase change main peak shown can show that the material prepared at this concentration of zinc sulfate solution can almost completely form a solid solution aluminum-zinc alloy; and the melting heat and solidification heat values of MEPCMs are both large, and the difference between the melting heat and the solidification heat is very small, indicating that the material has excellent thermal storage density and low supercooling, which is conducive to ensuring high energy storage density and improving heat conduction efficiency. That is to say, the heat storage and release temperature range of the material is located in the temperature range, and the expected effect of regulating the thermal storage temperature range is achieved; and the melting heat and solidification heat values of the core-shell structure Al-Zn@Al2O3 aluminum-zinc alloy phase change thermal storage material still maintain the original high values, and the difference between the melting heat and the solidification heat is very small, indicating that the material has excellent thermal storage density and low supercooling, which is conducive to improving heat storage and heat conduction efficiency.
[0051] Embodiment 3: A method for preparing a core-shell structure Al-Zn@Al2O3 composite phase change thermal storage material, the specific steps are as follows:
[0052] (1) respectively adding aluminum powder, hydrochloric acid, NH4F, zinc sulfate, and ethylenediaminetetraacetic acid into deionized water to prepare aluminum powder turbid solution, HCl solution, NH4F solution, ZnSO4 solution, and ethylenediaminetetraacetic acid solution; wherein the molar ratio of aluminum powder, hydrochloric acid, NH4F, zinc sulfate, and ethylenediaminetetraacetic acid is 92:20:20:56:62, the concentration of HCl in hydrochloric acid is 0.2 mol / L, the concentration of NH4F solution is 0.2 mol / L, the concentration of ZnSO4 solution is 0.56 mol / L, and the concentration of ethylenediaminetetraacetic acid solution is 0.62 mol / L;
[0053] (2) placing the aluminum powder turbid solution in an ultrasonic bath for 30 min to obtain an aluminum powder suspension; wherein the ultrasonic power is 70 W;
[0054] (3) adding HCl solution to the aluminum powder suspension, stirring at 65° C. for 5 min, then adding gelatin and reacting at 65° C. for 10 min under stirring to obtain solution A;
[0055] (4) At a temperature of 60° C. and under stirring conditions, NH4F solution was slowly added to solution A at a drop rate of 5 mL / min and the reaction was continued for 50 min, and then zinc sulfate solution and ethylenediaminetetraacetic acid solution were added at a drop rate of 4 mL / min and reacted for 5 h. The solution was allowed to stand for 40 min, solid-liquid separation was performed, and the solid was washed three times in the order of anhydrous ethanol-water-anhydrous ethanol, and then dried in vacuo at 60° C. to obtain solid B;
[0056] (5) Under protective atmosphere (argon), solid B is heated at a rate of 15°C / min to a temperature of 650°C and calcined for 2 h to obtain aluminum-zinc alloy powder;
[0057] (6) In an air atmosphere, the aluminum-zinc alloy powder was uniformly heated at a heating rate of 12°C / min to a temperature of 850°C and calcined for 1.5 h to obtain an Al-Zn@Al2O3 high-temperature phase change thermal storage material with a core-shell structure;
[0058] The DSC heat absorption and release characteristics of the core-shell structure Al-Zn@Al2O3 composite phase change thermal storage material prepared in this embodiment are shown in the figure. Figure 3 As shown, from Figure 3 Curve O-3 shows that the endothermic peak is 618.5℃, and the main exothermic peak is at 593℃, which means that the heat storage and release temperature range of the material is located near this temperature range. The single endothermic and exothermic peak shows that at this galvanizing amount, the aluminum-zinc alloy formed is almost completely composed of a single phase of solid solution alloy of zinc melted in aluminum. This shows that the phase change temperature can be adjusted to 618.5℃ by further increasing the galvanizing amount. Therefore, the MEPCMs prepared in this study have excellent applicability and controllability in medium and high temperature heat storage. The melting heat and solidification heat values of the core-shell structure Al-Zn@Al2O3 aluminum-zinc alloy phase change heat storage material still maintain the original high values, and the difference between the melting heat and the solidification heat is very small, indicating that the material has excellent heat storage density and low supercooling, which is conducive to improving energy storage and conduction efficiency.
[0059] The XRD spectra of Al@Zn and aluminum-zinc alloy powders prepared in Examples 1 to 3 are shown in Figure 4 , where Figure (a) is Al@Zn. After galvanizing, all samples have both Al phase (JCPDS No.04-0787) and Zn phase (JCPDS No.04-0831). As the zinc sulfate content required for the reaction increases (sample spectrum from bottom to top), the zinc plating amount on the sample surface increases after reduction. It can be observed from Figure (a) that the peak intensity corresponding to zinc increases accordingly, and the analysis results are consistent with reality; Figure (b) is aluminum-zinc alloy powder, from Figure 4 It can be seen that the peak of Al in the alloy and the corresponding peak of Al-Zn that is offset from the Al peak are detected in all samples, and it can be observed that the characteristic peak of Al in the alloy decreases with the increase of the molar fraction of zinc in the alloy, and the melting point of the alloy decreases with the increase of zinc concentration.
[0060] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. A method for preparing a core-shell structure Al-Zn@Al2O3 composite phase change thermal storage material, characterized in that: The specific steps are as follows: (1) Deionized water or ultrapure water are used to prepare aluminum powder turbid solution, HCl solution, NH4F solution, ZnSO4 solution and EDTA mixed solution respectively; (2) placing the aluminum powder turbid solution in an ultrasonic bath for 10 to 30 minutes to obtain an aluminum powder suspension; (3) adding HCl solution to the aluminum powder suspension, stirring at a temperature of 45 to 65° C. for 5 to 10 minutes, then adding gelatin and reacting at a temperature of 45 to 65° C. for 10 to 20 minutes under stirring to obtain solution A; (4) slowly adding NH4F solution to solution A at a temperature of 40 to 60° C. and stirring, and continuing the reaction for 30 to 60 minutes, then adding a mixture of zinc sulfate solution and ethylenediaminetetraacetic acid and reacting for 3 to 5 hours, standing, separating the solid and the liquid, washing the solid alternately with anhydrous ethanol-water-anhydrous ethanol for 3 to 5 times, and drying to obtain solid B; (5) In a protective atmosphere, the solid B is heated at a uniform rate to a temperature of 600 to 660° C. and calcined at high temperature for 0.5 to 4 h to obtain an aluminum-zinc alloy powder; (6) In an air atmosphere, the aluminum-zinc alloy powder is heated at a uniform rate to a temperature of 750-850°C and calcined for 1-4 h to obtain an Al-Zn@Al2O3 high-temperature phase change thermal storage material with a core-shell structure.
2. The method for preparing the core-shell structure Al-Zn@Al2O3 composite phase change thermal storage material according to claim 1, characterized in that: Step (1) The molar ratio of aluminum powder, hydrochloric acid, NH4F, zinc sulfate and EDTA is 92:(5~20):(15~25):(20~60):(30~70), the concentration of HCl solution is 0.05~0.20 mol / L, the concentration of NH4F solution is 0.15~0.25 mol / L, the concentration of ZnSO4 solution is 0.28~0.56 mol / L, and the concentration of EDTA solution is 0.31~0.62 mol / L.
3. The method for preparing the core-shell structure Al-Zn@Al2O3 composite phase change thermal storage material according to claim 1, characterized in that: The mass ratio of gelatin to aluminum powder in the aluminum powder suspension in step (3) is 1:(2-50).
4. The method for preparing the core-shell structure Al-Zn@Al2O3 composite phase change thermal storage material according to claim 1, characterized in that: The dropping rate of the NH4F solution in step (4) is 2-5 mL / min.
5. The method for preparing the core-shell structure Al-Zn@Al2O3 composite phase change thermal storage material according to claim 1, characterized in that: The dropping rate of the mixed solution of zinc sulfate solution and ethylenediaminetetraacetic acid in step (4) is 2-5 mL / min.
6. The method for preparing the core-shell structure Al-Zn@Al2O3 composite phase change thermal storage material according to claim 1, characterized in that: The protective atmosphere in step (5) is N2 atmosphere or inert atmosphere, and the uniform heating rate is 5 to 30°C / min.
7. The method for preparing the core-shell structure Al-Zn@Al2O3 composite phase change thermal storage material according to claim 1, characterized in that: The uniform heating rate in step (6) is 5 to 30°C / min.
Citation Information
Patent Citations
Preparation method and application of core-shell-structured Al-Cu@NiO-Al2O3 high-temperature phase-change heat-accumulation catalyst
CN109261165A
High-temperature composite phase-change heat storage material with multi-core-shell structure, and preparation method and application thereof
CN111718692A
Aluminum-based metal phase change microcapsule heat storage particles and preparation method
CN115780800A
Preparation method of Al-Cu-coated CuO composite phase change heat storage material with core-shell structure
CN116179171A
Microcapsule for latent heat storage materials, method for producing same, powder containing microcapsules for latent heat storage materials, and heat storage device comprising said powder
US20220298401A1